Health and well-being in eye care practice: Riding the emotional rollercoaster of the contact lens journey. Issue 10 (October 2021) - Tanna-Shah, Sheena; Retallic, Neil
Abstract : In the last in their series of articles looking at the influence of mental health and well-being upon clinical practice, Sheena Tanna-Shah and Neil Retallic discuss how we can best personalise, support and influence new wearer's experiences to increase compliance, maximise the chance of success and reduce the likelihood of early contact lens drop out.